Growth curves and their associated weight and height factors in children from birth to 4 years old in West Azerbaijan Province, northwest Iran - Ghaemmaghami, P.; Ayatollahi, S.M.T.; Alinejad, V.; Sharafi, Z. (Archives de pédiatrie : organe officiel de la Société française de pédiatrie, 2018)
Growth trajectory standards are important components that need to be monitored for suitable child growth. This study examined longitudinal data to identify the factors affecting growth trajectory standards of height and weight for infants. This study included 566 neonates (286 boys and 280 girls) born in West Azerbaijan Province, northwest Iran, who were followed from birth to 4 years of age. The subjects’ weight and height were recorded at birth, 1, 2, 4, 6, 9 months and 1, 1.5, 2, 3, and 4 years of age. In this study, the Lambda-Mu-Sigma (LMS) method was used to construct the growth curves for each measure. The linear mixed model was employed to determine the factors affecting the growth trajectory. The study demonstrates that the place of birth, duration of breastfeeding, and infants’ gender had a significant effect on the growth trajectory. Nonetheless, other variables did not have any significant effect on growth. Growth curves for significant factors of weight and height (5th, 50th, 95th percentiles) were obtained. There was a rapid increase in the growth curve from birth to 2 years of age, which then remained relatively constant up to 4 years of age. This paper provides the first local growth trajectory standards of height and weight for infants by analyzing longitudinal measurements in West Azerbaijan province. This study determined the factors affecting the growth trend in both indices. It seems that there was a significant difference in the growth trajectories of infants in subgroups of the effective factor.